UPAYA MENINGKATKAN KINERJA ANGGOTA PADA BAGIAN PEMELIHARAAN ALAT UTAMA SISTEM SENJATA MILITER DI LANUD HALIM PERDANAKUSUMA - Udariyanto, Diky Dwi; Akhmad, Jazuli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The purpose of the research is to analyze the performance, find out why the performance of members is less than optimal, formulate efforts to improve the performance of members in the maintenance section of the military defense equipment. The research approach used by the researcher is a qualitative approach. The data source that will be selected is focusing on the bearers of the human resource function, especially those in charge of evaluating the performance of personnel. Data collection techniques using observation methods, in-depth interviews, and document studies. The data analysis technique using interactive analysis according to Milles and Hubermen consists of three paths, namely: data reduction, data presentation and conclusion drawing/verification. The results showed that the performance of the Military Alutsista Maintenance Section was good but still less than the maximum seen from the achievements and elements of the success of the Members in the Military Alutsista Maintenance section in resolving the cases of the Members in the Military Alutsista Maintenance section and investigations. The causes of the quality of Members in the Maintenance of Military Alutsista are not optimal are the elements of success of Members in the Maintenance of Military Alutsista in resolving cases of Members in the Maintenance of Military Alutsista and investigations, Achievements that are still not optimal, Assessment of the implementation of the performance management sistem which is judged from the rewards obtained members in the maintenance section of the Military Alutsista are still not good and optimal. Efforts to improve the quality of Members in the Military Alutsista Maintenance section are complying with disciplinary regulations, maximizing the environmental atmosphere, maximizing existing infrastructure facilities in carrying out activities, a good assessment is also found in the application of a feedback performance management sistem from leadership coaching, making various efforts to fostering Members in the Maintenance of Military Alutsista.